Analysis of the Indonesian Supreme Audit Institution’s Strategic Response to the SDGs Program - Rahman, A.; Elfajri, W.; Kartika, R.; Yuskar, Yuskar (Economic Education Analysis Journal, 2023)
This study aims to map the strategic response of the Supreme Audit Institution of the Republic of Indonesia (Indonesian SAI) contained in the strategic plan to SDG issues. Then this research analyzes which of the 17 SDGs targets are the focus of BPK's performance audit. Finally, it analyzes the alignment of BPK's strategic responses that appear in the strategic plan document with the implementation of BPK's performance audit related to SDGs. This research was conducted using a thematic analysis approach, using NVIVO software. The results of the study provide input to BPK policy or regulation, namely so that the strategic responses that appear in the Indonesian SAI’s Strategic Plan and the selected audit policies are in line with the concept of Sustainable Development Goals.